Cataract Surgical Outcomes from a Large-scale Micro-surgical Campaign in China. (October 2013) - Xiao, Baixiang; Guan, Chunhong; He, Yaling; Le Mesurier, Richard; Müller, Andreas; Limburg, Hans; Iezze, Beatrice
Abstract Purpose: To assess cataract surgical outcomes during the Jiangxi Provincial Government's "Brightness and Smile Initiative" (BSI) in South East China during May 2009 to July 2010. Method: This cross sectional combined with retrospective study included 1157 cataract surgical patients (1254 eyes) recruited from six counties in Jiangxi during the initiative. Patient information before surgery and at discharge was obtained from hospitals' case records. Patient follow-up eye examinations were conducted during field visits in the autumn of 2010. Fifteen months after the initiative started, study subjects were examined by provincial ophthalmologists using a Snellen visual chart, portable slit lamp, torch and ophthalmoscope. The World Health Organization (WHO) cataract surgical outcome monitoring tally sheet and the outcome categories good (visual acuity, VA, ≥0.3 (6/18)), borderline (VA <0.3 but ≥0.1 (6/60)) and poor (VA < 0.1) were used for data collection and analysis. Results: A total of 99.7% of operated patients had intraocular lenses implanted. The percentage of eyes with good outcomes (presenting VA) at follow-up was low (49.6%), while the borderline and poor outcome rates were high (34.1% and 16.3%, respectively), in comparison to WHO recommendations. There was a significant outcome difference at follow-up (p < 0.01) between eyes operated by county surgeons trained by an International Non-Government Organization and those operated on by other visiting surgeons. Conclusions: This study documented a low rate of good cataract surgical outcomes from the BSI in Jiangxi. The quality of cataract surgery should be improved further in the province.